A Simulation Study on the Swelling and Shrinking Behaviors of Nanosized Montmorillonite Based on Monte Carlo and Molecular Dynamics. (15th September 2021) - Tong, Kaiwen; Guo, Jianhua; Chen, Shanxiong; Yu, Fei; Li, Shichang; Dai, Zhangjun
Abstract : Montmorillonite is the main mineral source for the swelling and shrinking of expansive soils. The macroscopic phenomena of soil are affected by the action of deep-level nanosized minerals. In order to illustrate the nanoscale mechanism from the molecular level, a combination of Monte Carlo and molecular dynamics was used to explore the swelling and shrinking characteristics of montmorillonite. The results showed that the basal spacing, free swelling ratio, and void ratio were positively correlated with water content but were inversely proportional to the change of CEC. The hysteresis phenomena of swelling and shrinking were the most significant at a water content of 40%. Compared with the expansive soil, the nanoscale shrinkage curve of montmorillonite also included three stages of normal shrinkage, residual shrinkage, and no shrinkage. The relative concentration of water molecules conveyed information such as the thickness and position of the hydration film and explained the difference in swelling and shrinking caused by the above variables. The changes in the number and length of hydrogen bonds revealed the order of formation and the process of destruction of hydrogen bonds during the reaction. The similarity of the trends between the basal spacing, binding energy, and the number of hydrogen bonds indicated that the swelling and shrinking of the crystal layer are a reflection of the molecular interaction, and the hydrogen bonding is particularly critical.